Introduction to Docker Compose (O'Reilly Media, Inc., 2022)
Containers are often advertised as solving a multitude of problems relating to delivering and maintaining highly available software in the always-on, global environment that most organizations must serve today, but how can they actually help you? What problems are you actually experiencing that can be solved with containers and its closely related technologies? After becoming comfortable with container basics, most organizations will want to start putting them to use in their development workflow, and even the most traditional monolithic application relies on at least one additional service, like a database. So, how can developers quickly, and reliably spin up a set of fully-configured containerized services on their local system? This class will introduce you to a tool called Docker Compose and teach you everything that you need to know about how to write a shareable docker-compose.yaml file that defines a set of related services which can be repeatably launched and torn down as needed.